rotl, an R package to interact with the Open Tree of Life data - Michonneau,François; Brown,Joseph W.; Winter,David (PeerJ Preprints, 2016)
1. While phylogenies have been getting easier to build, it has been difficult to re-use, combine, and synthesize the information they provide because published trees are often only available as image files, and taxonomic information is not standardized across studies. 2. The Open Tree of Life (OTL) project addresses these issues by providing a digital tree that encompasses all organisms, built by combining taxonomic information and published phylogenies. The project also provides tools and services to query and download parts of this synthetic tree, as well as the source data used to build it. Here, we present rotl, an R package to search and download data from the Open Tree of Life directly in R. 3. rotl uses common data structures allowing researchers to take advantage of the rich set of tools and methods that are available in R to manipulate, analyze, and visualize phylogenies. Here, and in the vignettes accompanying the package, we demonstrate how rotl can be used with other R packages to analyze biodiversity data. 4. As phylogenies are being used in a growing number of applications, rotl facilitates access to phylogenetic data, and allows their integration with statistical methods and data sources available in R.
Keywords: phylogenetics; API; R; comparative methods